Analisis Car Free Day dalam Meningkatkan Pendapatan UMKM di Karangpawitan Karawang - Jamal Handitia Putra; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze how Car Free Day (CFD) activities can increase the income of MSMEs (Micro, Small, and Medium Enterprises) in Karangpawitan, Karawang. The research method uses a qualitative descriptive approach with purposive sampling technique. From a total population of 155 MSME owners, 38 respondents were selected based on specific criteria: they must have been selling in the area for at least two years, were willing to be interviewed, and represented one to two similar types of MSMEs. The research findings show that CFD has a significant impact on increasing MSME income. MSME owners who have other business locations experienced income increases ranging from 25% to 85%, while MSME owners based in Karangpawitan recorded increases of up to 700%. The highest increases occurred in December at 50% and April at 49%, coinciding with year-end holidays and Eid al-Fitr celebrations. Enterprises related to children’s entertainment and culinary sectors experience the most significant growth. This research reveals that CFD not only serves as a public space for social and sports activities but also becomes a strategic opportunity for MSMEs to increase their income and expand their market reach.